CSR Disclosure on Earnings Management with the Presence of Women in the GCG Structure - Wahyuningsih, Alit; Rasmini, Ni Ketut (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 2 (2020), 2020)
This study examines the effects of Corporate Social Disclosure (CSR) on earnings management with the presence of woman in the Good Corporate Governance (GCG) as moderating variable. The sampling method used was purposive sampling with the criteria of companies listed in the LQ45 index on the Indonesia Stock Exchange and published annual reports and sustainability reports during 2013-2017 period. The data analysis technique used is Moderated Regression Analysis. This study concludes that disclosure of CSR has a positive effect on earnings management. CSR disclosure if accompanied by the presence of women on the audit committee that represents a proxy for the variable of the presence of women in the GCG structure negatively affects earnings management. The results of this study are in line with the theory of the political cost hypothesis which states that companies that have high political costs tend to do earnings management. Keywords: Earnings management, disclosure of corporate social responsibility, good corporate governance